EFEKTIVITAS PESAN KAMPANYE INDONESIA TANPA PACARAN TERHADAP MINAT NIKAH MUDA DIKALANGAN GENERASI Z - Nikmah Afiana Tridarmaningrum (Universitas Mercu Buana, 2022)
One of them is the @indonesiawithout dating account which positions its account as a syiar media for young people dating. This account activity is not only in the digital world but also penetrates into the real world through the form of self-actualization of the members of the @indonesiawithout dating account. This study aims to find out and explain the effectiveness of the Indonesia Without Dating campaign message on Young Marriage Interests for Generation Z (Study on followers of the @indonesiawithout dating Instagram account). This research is a quantitative explanatory using a survey research approach. Researchers used 100 respondents as samples with the Simple Randomized Probability Technique (Morrisan, 2015) The results of this study can be said that the campaign message for the Instagram account Indonesia Without Dating is effective in encouraging interest in young marriage in generation Z. This is in accordance with the results of the Spearman correlation analysis of 0.751 from Critical Values (Rs) of 0.197. In addition, there is a positive relationship between the variables X and Y from the positive values resulting from the test.